Patterns of coronary vascular involvement in patients with heart failure due to cardiac amyloidosis. (25th November 2020) - Yacob, O; Beyene, S; Melaku, G; Hideo-Kajita, A; Kuku, K; Brathwaite, E; Wilson, V; Ozaki, Y; Dan, K; Sheikh, F; Mohammed, S; Garcia-Garcia, H
Abstract: Background: Amyloidosis is a group of protein-folding disorders characterised by organ deposits, derived from one of several amyloidogenic precursor proteins. The involvement of coronary arteries has been previously described in amyloidosis, however the pattern of the disease in the coronaries is still unknown. Purpose: The aim of this study is to characterise the pattern and severity of coronary artery lesions in cardiac amyloidosis. Methods: We retrospectively compared patients with heart failure who tested positive (i.e. biopsy or gene tests – HF/CA+) against those that tested negative (HF/CA−) for cardiac amyloidosis. Groups were compared demographically and angiographically for qualitative and quantitative variables to determine patterns of involvement in the major epicardial coronary vessels. Results: In total, 110 heart failure patients were included in the study, of whom 55 were HF/CA+ patients (88 lesions) and 55 were HF/CA− patients (66 lesions). Despite the advanced age in the HF/CA+, (74.53±11.02 vs 54.11±15.08; p=0.05), severe calcification was reported in HF/CA− group (4.5% vs to 0.0%; p=0.018). The HF/CA+ group also had fewer ostial lesions (3.4% vs. 15.15%, p=0.0095), reduced TIMI flow grade (83% vs 76%; p=0.21) and a higher TIMI frame count (30±12 Vs 27±11 frames; p=0.06). In the HF/CA+ group, compared to women, men had a significant number of tandem lesions (14.55% vs 0.0%, p=0.02). Men trended to have more ulcerations in comparison to women (9.09% vs 0.0%; p=0.15). Conclusion: Overall, patients with HF/CA+ were older but found to have lesser calcified lesions, ostial involvement and a reduced anterograde blood flow. This is the first report outlining the coronary lesions in patients with HF/CA+. Funding Acknowledgement: Type of funding source: None